Personality Development at Work: Workplace Conditions, Personality Changes, and the Corresponsive Principle. Issue 1 (8th April 2013) - Le, Kimdy; Donnellan, M. Brent; Conger, Rand
Abstract Investigations concerning adult personality development have increasingly focused on factors that are associated with apparent personality trait changes. The current study contributes to this literature by replicating and extending previous research concerning personality trait development in young adulthood and perceptions of workplace conditions. Analyses were based on up to 442 individuals who participated in the ongoing Family Transitions Project (e.g., Conger & Conger, 2002). The current analyses included personality trait data from 1994 and 2003, high school grades and socioeconomic status indicators from 1994, and reports about work conditions in 2001, 2003, and 2005. Personality attributes were prospectively associated with work conditions and income. Findings also support the corresponsive principle of personality development (e.g., Roberts, Caspi, & Moffitt, 2003): Traits that were prospectively associated with particular workplace conditions often seemed to be accentuated by those conditions. Personality traits are prospectively associated with perceptions of the workplace. Workplace conditions are also associated with trait development.